2022
DOI: 10.1097/ans.0000000000000416
|View full text |Cite
|
Sign up to set email alerts
|

“Be Strong My Sista'”

Abstract: The experience of chronic pain is influenced by gender, race, and age but is understudied in older Black women. Society and family alike expect Black older women to display superhuman strength and unwavering resilience. This qualitative study examined the narratives of 9 rural- and urban-dwelling Black older women to identify the ways in which they displayed strength while living with chronic osteoarthritis pain. Their “herstories” parallel the 5 characteristics of the Superwoman Schema/Strong Black Woman. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…However, as argued within two studies included in this review, 37 , 38 it is not enough to simply consider gender. Gender is but one social factor that shapes experiences of chronic pain; it intersects with and is intersected by various other social identities.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, as argued within two studies included in this review, 37 , 38 it is not enough to simply consider gender. Gender is but one social factor that shapes experiences of chronic pain; it intersects with and is intersected by various other social identities.…”
Section: Resultsmentioning
confidence: 96%
“…Considering our focus on marginalization and EDI, we highlight those studies that exclusively focused on women, Indigenous Peoples, Black people, and people of colour, as these studies confront legacies of racism and sexism within chronic pain research. Within the studies included in this scoping review, 14 exclusively focused on women (20.8%), 32–45 12 exclusively focused on Black people (17.9%), 27 , 29 , 35 , 37 , 38 , 46–52 three exclusively focused on Indigenous Peoples (4.4%), 53–55 and six exclusively focused on people of color (8.9%). 42 , 45 , 56–59 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to investigate whether particular biopsychosocial variables are more or less strongly associated with pain in disparate racial groups, given that previous studies have documented unique pain experiences across such groups. 4,8 Moreover, several previous studies have suggested that the contribution of pain-related risk factors may differ across racial groups in the United States. 3,13 Accordingly, analyses of group differences in pain and its correlates in the present study controlled for critical factors such as exposures during and after participants' playing years.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors did not reference the lived experience of Black women or adequately contextualize the historical invisibility required of Black women to exist in the US’s racial contract . As the authors posit, routine use of patient-reported outcomes is a possible solution, but cultural and racial decolonization surrounding expectations of how patients report and clinicians engage in communication about symptoms is needed to generate diverse solutions informed by the voices of racialized communities .…”
mentioning
confidence: 99%